Biomimetic chitosan with biocomposite nanomaterials for bone tissue repair and regeneration - Kim, Se-Kwon; Murugan, Sesha Subramanian; Dalavi, Pandurang Appana; Gupta, Sebanti; Anil, Sukumaran; Seong, Gi Hun; Venkatesan, Jayachandran (Beilstein Journal of Nanotechnology, 2022)
Biomimetic materials for better bone graft substitutes are a thrust area of research among researchers and clinicians. Autografts, allografts, and synthetic grafts are often utilized to repair and regenerate bone defects. Autografts are still considered the gold-standard method/material to treat bone-related issues with satisfactory outcomes. It is important that the material used for bone tissue repair is simultaneously osteoconductive, osteoinductive, and osteogenic. To overcome this problem, researchers have tried several ways to develop different materials using chitosan-based nanocomposites of silver, copper, gold, zinc oxide, titanium oxide, carbon nanotubes, graphene oxide, and biosilica. The combination of materials helps in the expression of ideal bone formation genes of alkaline phosphatase, bone morphogenic protein, runt-related transcription factor-2, bone sialoprotein, and osteocalcin. In vitro and in vivo studies highlight the scientific findings of antibacterial activity, tissue integration, stiffness, mechanical strength, and degradation behaviour of composite materials for tissue engineering applications.
Keywords: antibacterial activity; biomimetic materials; bone graft substitutes; chitosan; gold; osteoinductive; silver